(untitled) (International Seven Journal of Multidisciplinary, 2024)
The New Digital Information and Communication Technologies and their applications in the teaching of chemistry have been highlighted as a contributor to the promotion of abstract concepts. In search of innovations that can contribute to the teaching of Optical Isomerism, we investigated the collaboration of the teaching of this concept provided in a didactic sequence with a CTS focus and with the support of a pedagogical didactic resource, the holographic pyramid for the representation of 3D images. The research was qualitative in nature and the target audience consisted of 35 high school students from a state school located in Vera Cruz do Oeste, Paraná. The students took part in two lessons that made up a didactic sequence addressing "Optical Isomerism and Medicines", and based on the data collected, we analyzed the construction of knowledge and the establishment of the relationships necessary for learning. The methods of analysis were based on the procedures of Discursive Textual Analysis, categorization was adapted and carried out a priori using the deductive method with support from Bloom’s Digital Taxonomy and the materials resulting from the application of the research were interpreted using the Double Coding Theory. We observed that some students contemplated the three levels of cognitive processing established by Paivio (1971): representational, referential and associative. However, for other students, we analyzed the need for different stimuli so that they could establish concrete connections. We suggest the Double Coding Theory for the analysis of teaching based on 3D images, contemplating the abstract concepts of Optical Isomerism and highlighting the importance of digital technology applied to chemistry teaching methods.